ANALYZING TRAUMA CASES AT GWERU PROVINCIAL HOSPITAL: WHAT DO ARIMA MODELS REVEAL (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study uses monthly time series data on trauma cases at Gweru Provincial Hospital (GPH) from Janaury 2010 to December 2018, to forecast trauma cases over the period January 2019 to December 2020. As shown by unit root tests, the series under consideration is basically an I (1) variable. The study applied the Box-Jenkins approach to time series forecasting and presented the ARIMA (0, 1, 2) model. Residual analysis of this model apparently indicates that the model is stable and thus suitable for predicting trauma cases at GPH over the out-of-sample period. The results of the study reveal that trauma cases will be in stable equilibrium of approximately 15 cases per month over the out-of-sample period. The study offers a two-fold policy recommendation in order to help the GPH management team in improving survival of trauma patients.